Gender Quotas, Autocracy, and the Status Quo: Explaining Why Morocco has had a More Positive Quota Experience than Jordan or Egypt. - Powers, Elizabeth K. (Tufts Archival Research Center, 2005)
The Arab world has the lowest percentage of female political participation. While the global average of women in parliament is just over 18%, the Arab region's average is only 9.5%. Certainly many Arab countries resemble each other in their long histories of patriarchy and authoritarian regime tendencies, and these similarities often prevent women's active participation in politics. However, one cannot claim that all Arab countries have identical experiences with gender quotas. Arab countries differ in their quota experiences, but few comparative studies have been conducted. In my research, I study the quota experiences of Jordan, Egypt, and Morocco. I discuss arguments that have been made as to why women should hold parliamentary office, why quotas are necessary, and how these arguments relate to Arab countries. While not enough time has passed to determine whether or not quotas in these countries are successful or if they empower women, I argue that as yet Morocco has had a more positive experience with gender quotas than either Jordan or Egypt. This may be explained by discrepancies between the countries' political institutions, including electoral systems, the autonomy of the women's movement and by the attitudes of the regimes toward gender quotas. Quotas have succeeded to a greater extent in Morocco than in the other two countries due to each of these factors, most importantly the regime's support for quotas. The strong Moroccan women's movement builds off of this support, or perhaps permissiveness, to give quotas a greater significance and impact than is found in the other cases. Quotas themselves are not capable of closing gender gaps and empowering women, but when applied in ideal circumstances they can bolster efforts to improve the status of women.